Regulation of Cell Wall-Bound Invertase in Pepper Leaves by Xanthomonas campestris pv. vesicatoria Type Three Effectors - Sonnewald, Sophia; Priller, Johannes; Schuster, Julia; Glickmann, Eric; Hajirezaei, Mohammed-Reza; Siebig, Stefan; Mudgett, Mary Beth; Sonnewald, Uwe (PLoS ONE, 2012)
Xanthomonas campestris pv. vesicatoria (Xcv) possess a type 3 secretion system (T3SS) to deliver effector proteins into its Solanaceous host plants. These proteins are involved in suppression of plant defense and in reprogramming of plant metabolism to favour bacterial propagation. There is increasing evidence that hexoses contribute to defense responses. They act as substrates for metabolic processes and as metabolic semaphores to regulate gene expression. Especially an increase in the apoplastic hexose-to-sucrose ratio has been suggested to strengthen plant defense. This shift is brought about by the activity of cell wall-bound invertase (cw-Inv). We examined the possibility that Xcv may employ type 3 effector (T3E) proteins to suppress cw-Inv activity during infection. Indeed, pepper leaves infected with a T3SS-deficient Xcv strain showed a higher level of cw-Inv mRNA and enzyme activity relative to Xcv wild type infected leaves. Higher cw-Inv activity was paralleled by an increase in hexoses and mRNA abundance for the pathogenesis-related gene PRQ. These results suggest that Xcv suppresses cw-Inv activity in a T3SS-dependent manner, most likely to prevent sugar-mediated defense signals. To identify Xcv T3Es that regulate cw-Inv activity, a screen was performed with eighteen Xcv strains, each deficient in an individual T3E. Seven Xcv T3E deletion strains caused a significant change in cw-Inv activity compared to Xcv wild type. Among them, Xcv lacking the xopB gene (Xcv Delta xopB) caused the most prominent increase in cw-Inv activity. Deletion of xopB increased the mRNA abundance of PRQ in Xcv Delta xopB-infected pepper leaves, but not of Pti5 and Acre31, two PAMP-triggered immunity markers. Inducible expression of XopB in transgenic tobacco inhibited Xcv-mediated induction of cw-Inv activity observed in wild type plants and resulted in severe developmental phenotypes. Together, these data suggest that XopB interferes with cw-Inv activity in planta to suppress sugar-enhanced defense responses during Xcv infection. Citation: Sonnewald S, Priller JPR, Schuster J, Glickmann E, Hajirezaei M-R, et al. (2012) Regulation of Cell Wall-Bound Invertase in Pepper Leaves by Xanthomonas campestris pv. vesicatoria Type Three Effectors. PLoS ONE 7(12): e51763. doi:10.1371/journal.pone.00517

The Xanthomonas campestris pv. vesicatoria Type-3 Effector XopB Inhibits Plant Defence Responses by Interfering with ROS Production. - Priller, Johannes; Reid, Stephen; Konein, Patrick; Dietrich, Petra; Sonnewald, Sophia (PLoS ONE, 2016)
The bacterial pathogen Xanthomonas campestris pv. vesicatoria 85-10 (Xcv) translocates about 30 type-3 effector proteins (T3Es) into pepper plants (Capsicum annuum) to suppress plant immune responses. Among them is XopB which interferes with PTI, ETI and sugar-mediated defence responses, but the underlying molecular mechanisms and direct targets are unknown so far. Here, we examined the XopB-mediated suppression of plant defence responses in more detail. Infection of susceptible pepper plants with Xcv lacking xopB resulted in delayed symptom development compared to Xcv wild type infection concomitant with an increased formation of salicylic acid (SA) and expression of pathogenesis-related (PR) genes. Expression of xopB in Arabidopsis thaliana promoted the growth of the virulent Pseudomonas syringae pv. tomato (Pst) DC3000 strain. This was paralleled by a decreased SA-pool and a lower induction of SA-dependent PR gene expression. The expression pattern of early flg22-responsive marker genes indicated that MAPK signalling was not altered in the presence of XopB. However, XopB inhibited the flg22-triggered burst of reactive oxygen species (ROS). Consequently, the transcript accumulation of AtOXI1, a ROS-dependent marker gene, was reduced in xopB-expressing Arabidopsis plants as well as callose deposition. The lower ROS production correlated with a low level of basal and flg22-triggered expression of apoplastic peroxidases and the NADPH oxidase RBOHD. Conversely, deletion of xopB in Xcv caused a higher production of ROS in leaves of susceptible pepper plants. Together our results demonstrate that XopB modulates ROS responses and might thereby compromise plant defence.